Leitura e motivação - Silva, Cláudia Gomes da (2007)
This research checked the relation between reading and motivation through indicators of internal motivation and interpretation of tests, chosen for classroom reading. We searched data that could show the influence of the motivation, or not, in the reader education. In the first moment, we loooked for information which characterized the readers' own self-image, his enviroment, reading preferences. Based on this last item, we chose the texts used in this study. An instrument, adapted to the purpose of this research, brought up data related to internal motivation. Then, the students went through texts to measure their level of motivation. After checking their performance, their low and high level of motivation, evidence was produced to confirm that motivacion really plays an important role in reading. The hypothesis was confirmed. Internal motivation is a meaningful element in reading. The result spotlights motivation as an important factor in reading in classroom at and at home. Motivation enables the student to elaborate this reading activity.